SINTESIS NANOPARTIKEL SERAT RAMI DENGAN METODE ULTRASONIKASI UNTUK APLIKASI FILLER BIONANOKOMPOSIT - D Kurniawan (Jurnal Biofisika, 2012)
Synthesis of nanoparticles was obtained from the hemp fiber ultrasonic method. Nanoparticles hemp fiber is used as bio-nanocoomposite Ultrasonic method of hemp fiber was done with the time variations of surfactant tween 80 3 % as many as 10 samples and 0 % as much as 3 samples. All samples were tested with the Particle Size Analyzer (PSA) to determine the size distribution. The smallest sized fiber was obtained from 105 min sonication with 3 % tween 80, the size is 229.04 nm. Hemp fiber size with concentration of tween 80 3 % smaller than the concentration of Tween 80 0 %. Hemp fibers with nanometer- size 229.04 has a density of 1.1727 g cm - 3 is smaller than 7500 nanometers in size hemp fibers with a density of 1.7083 g cm - 3 . Results of X - ray Diffraction ( XRD ) showed the smallest size hemp fiber hemp is a cellulose fiber , characterized by their crystal phase cellulose is at 22.76 degrees diffraction angle with the degree of crystallinity 21.3727 %